2015
DOI: 10.1080/10503307.2015.1072283
|View full text |Cite
|
Sign up to set email alerts
|

Favourable outcome of long-term combined psychotherapy for patients with borderline personality disorder: Six-year follow-up of a randomized study

Abstract: Objective: This study reports the six-year follow-up data of patients with borderline personality disorder (BPD) who participated in the Ullevål Personality Project (UPP), a randomized clinical study comparing outpatient individual psychotherapy (OIP) with a long-term combination programme (CP) comprising short-term day-hospital treatment followed by outpatient combined group and individual psychotherapy. Methods: For 52 patients, outcomes were evaluated after 8 months, 18 months, 3 years, and 6 years based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…groups who received a combination of day hospital and outpatient treatment [19,20]. The hours of formal therapy fluctuated between 60 and over 600 h, the latter reported by the MBT trial [20].…”
Section: Treatment Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…groups who received a combination of day hospital and outpatient treatment [19,20]. The hours of formal therapy fluctuated between 60 and over 600 h, the latter reported by the MBT trial [20].…”
Section: Treatment Interventionsmentioning
confidence: 99%
“…In addition to naturalistic research, clinical trials of psychotherapeutic interventions for BPD have recently shown greater interest in their long-term outcomes, reporting follow-up data for five years or more [19, 20, 21, 22, 23]. This longitudinal perspective on efficacy studies underlines the relevance of treatment as a potential factor of change over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence-based treatments for BPD, e.g., dialectical-behavioral therapy (DBT), schema-focused therapy (SFT), and mentalization-based therapy (MBT) utilize group components. Its beneficial effects on social perception and interpersonal skills in various settings, e.g., outpatient and inpatient treatment, have been outlined ( Farrell et al, 2009 ; Bateman and Fonagy, 2010 ; Bloom et al, 2012 ; Karterud and Bateman, 2012 ; Laurenssen et al, 2014 ; Kvarstein et al, 2015 ; Linehan and Wilks, 2015 ; Dimaggio and Brune, 2016 ; Fassbinder et al, 2016 ; Kramer et al, 2016 ; Antonsen et al, 2017 ; Edel et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Groups focused on insight and interpersonal work can help patients learn about maladaptive self‐states and relational patterns that may hinder their adjustment to various social roles. Programmes with groups targeting reflective abilities (e.g., regarding underlying mental states and relational dynamics) have been found to produce positive effects for improved social functioning (Popolo et al, ), including at long‐term follow‐up (Antonsen et al, ).…”
Section: Introductionmentioning
confidence: 99%